Hak Cipta Atas Karya Digital: Kajian Yuridis terhadap Pembajakan Konten di Media Sosial - Mohamad Hanif Naufal Maemunah (Jurnal Riset Ilmu Hukum, 2025)
Abstract. The development of information technology and the extensive use of social media have significantly transformed the distribution of digital copyrighted works, while simultaneously generating serious challenges for copyright protection. The practice of digital content piracy, including videos, images, music, and written works, has increasingly occurred on social media platforms without the authorization of copyright holders, resulting in economic losses and weakening legal certainty. This study aims to examine the legal protection of copyright over digital works and to assess the effectiveness of law enforcement against content piracy on social media. This research employs a normative legal approach using a juridical-normative method, with statutory and case approaches, focusing on Law Number 28 of 2014 on Copyright and relevant court decisions concerning digital copyright infringement. The findings indicate that although Indonesia has established a relatively adequate normative framework for copyright protection, its implementation remains ineffective due to weak law enforcement, low public legal awareness, and the absence of clear regulations governing the responsibilities of digital platforms. Therefore, this study recommends strengthening legal regulations, improving law enforcement capacity, and enhancing collaboration between the government and digital platform providers to ensure effective and sustainable copyright protection in the digital environment. Abstrak. Perkembangan teknologi informasi dan penggunaan media sosial telah menghadirkan peluang sekaligus tantangan dalam perlindungan hak cipta atas karya digital. Praktik pembajakan konten termasuk video, gambar, musik, dan tulisan semakin marak terjadi tanpa izin pemilik hak, sehingga menimbulkan kerugian bagi pencipta dan mengurangi insentif berkreativitas. Penelitian ini bertujuan untuk mengkaji perlindungan hukum terhadap hak cipta atas karya digital serta menilai efektivitas penegakan hukum terhadap pembajakan konten di media sosial. Penelitian ini menggunakan pendekatan hukum normatif dengan metode yuridis normatif melalui kajian perundang-undangan dan studi kasus, khususnya terhadap Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta dan putusan pengadilan terkait pelanggaran hak cipta digital. Hasil penelitian menunjukkan bahwa meskipun Indonesia telah memiliki kerangka hukum yang relatif memadai secara normatif, implementasinya belum optimal karena lemahnya penegakan hukum, rendahnya literasi hukum masyarakat, serta belum adanya peraturan yang mengatur kewajiban tanggung jawab platform digital secara jelas. Penelitian ini merekomendasikan penguatan regulasi dan kolaborasi antara pembuat kebijakan, aparat penegak hukum, dan penyedia platform digital guna mewujudkan sistem perlindungan hak cipta digital yang efektif di era teknologi informasi.